An Analytical Approach for Design of Microstrip Patch (MsP) - R. J. Kavitha; H. S. Aravind (Institute of Advanced Engineering and Science, 2018)
A reliable configuration of electromagnetic interactions for antenna design can yield an effective Microstrip patch (MsP) antenna. During its design, the antenna arrays involve issues with parameters (i.e., space, dimension, shape) adjustment. This problem can be tackled with an analytical approach which can help to bring better idea to design the antenna aaray. However, the realistic designs of antenna array are quite expensive while extracting computational accuracy. Thus, to have low cost computational accuracy various meta-heuristic (generic algorithm, partical swarm optimizarion) approaches are used and are considered as effective one in handling the pattern synthesis problems. Howeever, the use of meta-heuristic approaches demands thousands of functions to analyze the antenna design. This manuscript introduces an analytical approach for MsP antenna desing using MATLAB that brings optimization in handling the side lobes and optimizing the reflection as well as radiation responses. The outcomes of the design were analyzed with respect to reflection, radiation coefficients, side lobes and found effective at 10GHz as per computational cost is concern.